ChroPac-trial: duodenum-preserving pancreatic head resection versus pancreatoduodenectomy for chronic pancreatitis : trial protocol of a randomised controlled multicentre trial - Diener, Markus K.; Bruckner, Thomas; Contin, Pietro; Halloran, Christopher; Glanemann, Matthias; Schlitt, Hans Jürgen; Mössner, Joachim; Kieser, Meinhard; Werner, Jens; Büchler, Markus W.; Seiler, Christoph (Trials, 2010)
Background: A recently published systematic review indicated superiority of duodenum-preserving techniques when compared with pancreatoduodenectomy, for the treatment of patients with chronic pancreatitis in the head of the gland. A multicentre randomised trial to confirm these results is needed. - Methods/Design: ChroPac aims to investigate differences in quality of life, mortality and morbidity during 24 months after surgery (duodenum-preserving pancreatic head resection versus pancreatoduodenectomy) in patients with chronic pancreatitis of the pancreatic head. ChroPac is a randomised, controlled, observer and patient blinded multicentre surgical trial with two parallel comparison groups. The primary outcome measure will be the average quality of life during 24 months after surgery. Statistical analysis is based on the intention-to-treat population. Analysis of covariance will be applied for the intervention group comparison adjusting for age, centre and quality of life before surgery. Level of significance is set at 5% (two-sided) and sample size (n = 100 per group) is determined to assure a power of 90%. - Discussion: The ChroPac trial will explore important outcomes from different perspectives (e.g. surgeon, patient, health care system). Its pragmatic approach promises high external validity allowing a comprehensive evaluation of the surgical strategy for treatment of patients with chronic pancreatitis.